A high tear resistance and high oil resistance double cross-linked halogen-free low smoke flame retardant cable material and its preparation method and application
By using specific ethylene copolymers and dual crosslinking processes in cable materials, the problem that existing cable materials are difficult to take into account both tear resistance and oil resistance is solved, and efficient flame retardant and mechanical performance improvement is achieved.
Patent Information
- Application Number
- CN202310668223.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Existing halogen-free low-smoke flame-retardant cable materials are difficult to take into account both tear resistance and oil resistance, and when the flame retardant performance is improved, the mechanical properties and tear resistance of the material will be affected.
Ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer and ethylene-glycerol methacrylate-vinyl acetate terpolymer were used as resin base materials, and silane self-crosslinking was performed first through the bi-crosslinking process. , and then cross-linking is used to form cable materials with high toughness, heat resistance and tear resistance.
It achieves a balance between high tear resistance and high oil resistance, while improving the flame retardant performance and mechanical properties of the material, solving the problem that traditional cable materials are difficult to balance between flame retardant and mechanical properties.
Smart Images

Figure BDA0004271688140000031 
Figure BDA0004271688140000032 
Figure BDA0004271688140000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a high tear resistance and high oil resistance double cross-linked halogen-free low smoke flame retardant cable material and a preparation method and application thereof. Background Art
[0002] With the continuous development of society and the widespread application of electrification technology, all walks of life have higher and higher requirements for the quality and performance of wires and cables. Especially in some special fields, such as ships, chemicals and marine engineering, these fields have special use environments and need to face harsh environments such as oil pollution, bumps, torsion, etc. during use, and need to withstand more severe tests. Therefore, these special fields not only require cables to have conventional properties such as safety, environmental protection, and halogen-free, but also have higher requirements for special properties such as flame retardancy, oil resistance, tear resistance, and low smoke.
[0003] In view of the stringent requirements for cables in such special fields, the corresponding cable sheath, as the most direct protective layer of the cable, needs to meet various performance requirements. However, there are contradictions in the various performances that are difficult to balance. How to meet the various physical and chemical properties required by such cables is a major problem in the field of cable materials.
[0004] To improve the flame retardant properties of materials, a large amount of flame retardants need to be added. For example, a Chinese patent with publication number CN110176329B discloses a flame retardant cable, which includes a conductor, an inner shielding layer, an inner insulating layer, an inner sheath, a filling, a wire core tape layer, an inner sheath, a braided shielding layer, and a flame retardant jacket from the inside to the outside, and the filling is a flame retardant material. The flame retardant jacket adopts a flame retardant cable material with an oxygen index of ≥38, and has a good flame retardant effect. It uses polyethylene as the main raw material, and uses alkalized fly ash and modified zirconium hydrogen phosphate powder to obtain a flame retardant powder. However, such addition of a large amount of flame retardants to the material to improve the flame retardant properties of the material will inevitably affect the mechanical properties, electrical properties and tear resistance of the material.
[0005] At present, most of the low-smoke halogen-free polyolefin cable materials are based on ethylene-vinyl acetate copolymer (EVA). For example, the Chinese patent with publication number CN109485989B discloses a cable material for photovoltaic cables and a preparation method thereof. The cable material for photovoltaic cables includes the following raw material components by weight: 10-40 parts of ethylene-vinyl acetate copolymer, 3-8 parts of polyolefin elastomer, 3-25 parts of polyethylene, 3-8 parts of compatibilizer, 40-65 parts of filler and 1-5 parts of cross-linking agent. The cable material is prepared by first mixing each raw material component through a mixer to form a material mass; then extruding and granulating through an extruder; then extruding into wire through an extruder, and finally irradiating and cross-linking. However, EVA generally has a low melting point and weak polarity. If you want to increase the polarity, you need to use EVA with a high content of vinyl acetate (VA). This method not only increases the cost, but also reduces the overall melting point of the material, which is not conducive to the oil resistance of the material.
[0006] At present, in order to solve the above-mentioned oil resistance problem, the prior art usually increases the irradiation dose of the material so that the material has a higher degree of crosslinking and thus improves its oil resistance. The patent with publication number CN114864163B discloses a high temperature resistant flame retardant cable, wherein the high temperature resistant layer is a irradiation crosslinked polyolefin material extruded on the insulating layer, and then the high temperature resistant layer is subjected to electron irradiation processing by electron acceleration using an irradiation crosslinking process, and the irradiation dose is 2.65MRad. However, the method of increasing the degree of crosslinking by increasing the irradiation dose, although it improves its degree of crosslinking and oil resistance, increases the irradiation dose also brings more stress concentration and structural damage, which greatly reduces the elongation at break and tear resistance of the material. At the same time, the free radicals generated during the high-dose irradiation process will consume a large amount of antioxidants and light stabilizers, further increasing the cost.
[0007] During the laying and use of cables, it is inevitable that bumps and other problems will occur. The tiny defects caused by the bumps will cause the cable sheath to tear under the action of a small external force. Therefore, it is very important to improve the tear resistance of the cable sheath material. For plastic low-smoke halogen-free materials after irradiation cross-linking, the tear resistance shows a maximum value as the degree of cross-linking increases, and this maximum value is reached at the beginning of cross-linking, so the tear resistance drops sharply thereafter. In order to ensure the oil resistance, aging resistance and other properties of the material, sufficient cross-linking degree is a necessary prerequisite, so there is an irreconcilable contradiction between the tear resistance and most properties. At present, the common measure taken for tear resistance is to add reinforcing materials, such as reinforcing carbon black, etc., but if you want to achieve a significant improvement effect, such reinforcing materials need to be added in large quantities, which also brings about a decline in mechanical properties, electrochemical properties, weather resistance and aging resistance. Therefore, there is no mature technology to solve this problem under the premise of ensuring cost and performance.
[0008] Therefore, it is urgent to develop and design a halogen-free, low-smoke, flame-retardant cable material with high tear resistance and high oil resistance to meet the needs of the above-mentioned special fields. Summary of the invention
[0009] In order to solve the problem that it is difficult to balance tear resistance and oil resistance in existing halogen-free low-smoke flame-retardant cables, the first purpose of the present application is to provide a high tear resistance and high oil resistance double cross-linked low-smoke halogen-free flame-retardant cable material. By selecting and compounding three ethylene copolymers with long side chain structures, namely ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer and ethylene-glyceryl methacrylate-vinyl acetate, sufficient toughness and softness can be provided to the material, so that the cable material of the present application can be toughened without adding elastomers compared to conventional flame-retardant cable materials.
[0010] The second purpose of the present application is to provide a method for preparing a highly tear-resistant and highly oil-resistant double-crosslinked low-smoke halogen-free flame-retardant cable material. The cable material is prepared by a double-crosslinking method, that is, in the early stage, a silane self-crosslinking method is adopted to allow the material to have a preliminary crosslinking network, and in the later stage, a radiation crosslinking method is adopted to improve the three-dimensional network structure of the material, thereby improving the uniformity of the microscopic network structure, so that it forms a highly elastic, strong, and well-structured CC bond and Si-O-Si bond interlaced intertwined intertransmission network, thereby enabling the material to have excellent heat oil resistance and tear resistance.
[0011] The third purpose of the present application is to provide a tear-resistant, highly oil-resistant, double-cross-linked, low-smoke, halogen-free flame-retardant cable material for use in cables, which can be used as a cable outer layer flame-retardant material and extruded outside the cable track, and has good mechanical properties, aging properties, hot oil resistance, tear resistance and flame retardant properties.
[0012] In order to achieve the first purpose of the present application, the present application provides a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, which adopts the following technical solution:
[0013] A high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, comprising the following raw materials in parts by weight:
[0014]
[0015] The resin base material comprises 10 to 30 parts of ethylene-ethyl acrylate copolymer, 10 to 30 parts of ethylene-butyl acrylate copolymer and 10 to 30 parts of ethylene-glycidyl methacrylate-vinyl acetate terpolymer.
[0016] Furthermore, the flame retardant cable material also includes:
[0017]
[0018] Furthermore, the resin base material also includes 5 to 25 parts of metallocene-catalyzed polyethylene and 15 to 25 parts of medium-density polyethylene.
[0019] Furthermore, the ethylene-ethyl acrylate copolymer is a mixture of ethylene-ethyl acrylate copolymers with an ethyl acrylate content of 15% and ethyl acrylate content of 25% in a mass ratio of 1:1.
[0020] Furthermore, the ethylene-butyl acrylate copolymer is a mixture of ethylene-butyl acrylate copolymers with a butyl acrylate content of 17% and butyl acrylate content of 27% in a mass ratio of (1:1) to (1:2).
[0021] Furthermore, the ethylene-glyceryl methacrylate-vinyl acetate terpolymer has a glyceryl methacrylate content of 12% and a vinyl acetate content of 5%.
[0022] Furthermore, the flame retardant includes 120 to 200 parts of a halogen-free flame retardant, 3 to 6 parts of an organosilicon flame retardant, and 3 to 12 parts of a nano synergist.
[0023] Furthermore, the average particle size of the halogen-free flame retardant is 0.6-2.0 μm.
[0024] Furthermore, the surface treatment agent is at least one of a vinyl silane coupling agent, an amino silane coupling agent and a titanate coupling agent.
[0025] In order to achieve the second purpose of the present application, the present application provides a method for preparing a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, which adopts the following steps:
[0026] Step S2: Preparation of mixed flame retardant filler
[0027] Fully mixing the flame retardant, the radiation cross-linking sensitizer, the unsaturated silane cross-linking agent and the silane cross-linking initiator to obtain a first mixed flame retardant filler;
[0028] Fully mixing the flame retardant, the radiation cross-linking sensitizer and the silane cross-linking catalyst to obtain a second mixed flame retardant filler;
[0029] Step S3: Preparation of material A
[0030] The first mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material A;
[0031] Step S4: Preparation of material B
[0032] The second mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material B;
[0033] Step S5: Extrusion molding
[0034] Blending and extruding the material A and the material B;
[0035] Step S6: Double cross-linking
[0036] The material extruded in step S5 is placed in an environment with a temperature of 23±2° C. and a humidity of 45% to 55% to perform silane self-crosslinking; after the silane self-crosslinking is completed, the sample is subjected to electron beam irradiation crosslinking.
[0037] Furthermore, in step S2, nano synergists, antioxidants, lubricants and light stabilizers may be added and mixed.
[0038] Furthermore, hollow glass microspheres and silicone masterbatch may be added and mixed in step S3 and step S4.
[0039] Furthermore, in the step S6, the irradiation process for irradiation cross-linking is 28 passes, 2.1 mev energy, 26 mA flow rate, and 70 m / min speed.
[0040] In order to achieve the third purpose of the present application, the present application provides a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material for use in cables, using the following steps:
[0041] Step S2: Preparation of mixed flame retardant filler
[0042] Fully mixing the flame retardant, the radiation cross-linking sensitizer, the unsaturated silane cross-linking agent and the silane cross-linking initiator to obtain a first mixed flame retardant filler;
[0043] Fully mixing the flame retardant, the radiation cross-linking sensitizer and the silane cross-linking catalyst to obtain a second mixed flame retardant filler;
[0044] Step S3: Preparation of material A
[0045] The first mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material A;
[0046] Step S4: Preparation of material B
[0047] The second mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material B;
[0048] Step S5: Extruding the Cable
[0049] The A material and the B material are mixed and placed in an extruder for extrusion;
[0050] Step S6: Double cross-linking
[0051] The material extruded in step S5 is placed in an environment with a temperature of 23±2° C. and a humidity of 45% to 55% to perform silane self-crosslinking; after the silane self-crosslinking is completed, the sample is crosslinked by electron beam irradiation.
[0052] Furthermore, the extrusion temperature of the extruder in step S5 is set to 130°C to 140°C in zone 1, 140°C to 150°C in zone 2, 145°C to 155°C in zone 3, 155°C to 165°C in zone 4, and 160°C to 170°C in the die.
[0053] In summary, the present application provides a high tear resistance and high oil resistance double cross-linked halogen-free low-smoke flame-retardant cable material and a preparation method and application thereof, which have the following beneficial effects:
[0054] In order to take into account the tear resistance, oil resistance and flame retardancy of cable materials, this application improves the raw materials and preparation process of flame retardant cables:
[0055] In terms of raw material selection, this application selects EEA, EBA and E-GMA-VA, three ethylene copolymers with long side chain structures, for compounding. EEA not only has a high melting point, but also has the highest toughness and softness among polyolefin resins. Compared with EVA, it has higher toughness and better thermal stability; EBA itself has high strength and wear resistance and excellent tear resistance; the use of EEA with high and low EA content and EBA with high and low BA content can not only ensure the mechanical properties of the material, but also improve the polarity of the resin base material and thus improve the compatibility with the flame retardant filler; at the same time, according to the hydrophilic and oleophobic characteristics of the polar group, Improve the oil resistance of the material. High EA and high BA content can provide support for the softness of the material. At the same time, the addition of EBA can extend the service life of the material. E-GMA-VA is a terpolymer with high reactivity, which can improve the later cross-linking efficiency and provide support for a more stable network structure. At the same time, E-GMA-VA has high adhesion and can better connect the functions of each component in series to improve the comprehensive performance of the material. The compound use of the above multiple ethylene copolymers can provide the material with sufficient toughness and softness, so that the cable material of the present application can be toughened without adding elastomers compared to conventional flame-retardant cable materials.
[0056] In terms of preparation technology, the present application adopts a double cross-linking method to prepare cable materials, that is, in the early stage, the silane self-crosslinking method is first used to allow the material to have a preliminary cross-linking network, and in the later stage, the irradiation cross-linking method is used to improve the three-dimensional network structure of the material, thereby improving the uniformity of the microscopic network structure, so that it forms a highly elastic, strong, and well-structured CC bond and Si-O-Si bond interlaced inter-transfer network, thereby making the material have excellent heat oil resistance and tear resistance. In addition, the early silane self-crosslinking process needs to ensure that the material cross-linking efficiency is high, but the overall cross-linking degree does not need to be too high, and only a preliminary cross-linking framework needs to be formed. Therefore, the amount of unsaturated silane cross-linking agent and silane cross-linking initiator added in terms of silane cross-linking is greatly reduced compared with the conventional silane cross-linking process.
[0057] Instruction Manual
[0058] Figure 1A Shown is a scanning electron microscope image of the flame retardant cable material prepared in Example 1 of the present application.
[0059] Figure 1B Shown is a scanning electron microscope image of the flame retardant cable material prepared in Example 2 of the present application.
[0060] Figure 1C Shown is a scanning electron microscope image of the flame retardant cable material prepared in Example 3 of the present application.
[0061] Figure 1D Shown is a scanning electron microscope image of commercially available cable material. DETAILED DESCRIPTION
[0062] In the following specific embodiments, if no specific experimental steps or conditions are indicated, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. The reagents or instruments used are not indicated by the manufacturer, and are all conventional reagent products that can be obtained commercially. The term "comprising" is intended to be open-ended, and can be replaced with "consisting of..." in appropriate cases. In this article, unless otherwise indicated, percentage refers to weight / weight percentage. Except in the examples, or otherwise clearly stated, all numbers indicating the mass of substances, physical properties, etc. in the specification and claims should be understood to be modified with "about".
[0063] In order to facilitate the data comparison between the examples and the comparative examples, the selection of raw materials is consistent, specifically:
[0064] Metallocene-catalyzed polyethylene was provided by DAELIM, model XP9400;
[0065] Medium-density polyethylene was provided by Borealis, model ME3400;
[0066] The maleic anhydride grafted compound was provided by Ruicheng, model number MG9215;
[0067] The silicone masterbatch is provided by Dow Corning, model number is MB50;
[0068] Hollow glass microspheres are provided by Huaxing, model D18000;
[0069] The present invention firstly discloses a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, which is formed by using an ethylene copolymer with a long side chain structure as a resin base material and then sequentially cross-linking through silane cross-linking and radiation cross-linking.
[0070] In some embodiments, the cable material may include the following raw materials in parts by weight:
[0071]
[0072]
[0073] The resin base material may include the following materials in parts by weight:
[0074]
[0075] In at least some embodiments, the resin base can be obtained by the following method:
[0076] In parts by weight, 10 to 30 parts of ethylene-ethyl acrylate copolymer (EEA), 10 to 30 parts of ethylene-butyl acrylate copolymer (EBA), 10 to 30 parts of ethylene-glycidyl methacrylate-vinyl acetate terpolymer (E-GMA-VA), 5 to 25 parts of metallocene-catalyzed polyethylene and 15 to 25 parts of medium-density polyethylene are fully mixed, placed in a reciprocating extruder silo, fed through a loss-in-weight scale, and extruded, granulated and dried to obtain a resin base material.
[0077] Preferably, the ethylene-ethyl acrylate copolymer (EEA) is a mixture of EEA with an ethyl acrylate (EA) content of 15% and EEA with an EA content of 25% in a mass ratio of 1:1; the ethylene-butyl acrylate copolymer (EBA) is a mixture of EBA with a butyl acrylate (BA) content of 17% and a BA content of 27% in a mass ratio of (1:1) to (1:2); the ethylene-glycidyl methacrylate-vinyl acetate terpolymer (E-GMA-VA) has a glycidyl methacrylate (GMA) content of 12% and a vinyl acetate (VA) content of 5%.
[0078] This application selects three ethylene copolymers with long side chain structures, namely EEA, EBA and E-GMA-VA, for compounding. EEA not only has a high melting point, but also has the highest toughness and softness among polyolefin resins. Compared with EVA, it has higher toughness and better thermal stability. EBA itself has high strength and wear resistance and excellent tear resistance. The compounding of EEA with high and low EA content and EBA with high and low BA content can not only ensure the mechanical properties of the material, but also improve the polarity of the resin base material and thus improve the compatibility with the flame retardant filler. At the same time, the hydrophilic and oleophobic properties of the polar group can improve the material. Oil resistance, high EA and high BA content can provide support for the softness of the material, and the addition of EBA can extend the service life of the material; E-GMA-VA is a terpolymer with high reactivity, which can improve the later cross-linking efficiency and provide support for a more stable network structure. At the same time, E-GMA-VA has high adhesion and can better connect the functions of each component in series to improve the comprehensive performance of the material; the compound use of the above multiple ethylene copolymers can provide the material with sufficient toughness and softness, so that the cable material of the present application can be toughened without adding elastomers compared to conventional flame-retardant cable materials.
[0079] In addition, the compounding of metallocene-catalyzed polyethylene and medium-density polyethylene can not only ensure the mechanical properties of the material, but also increase the melting temperature of the material, thereby improving the material's high-temperature oil resistance.
[0080] In some preferred embodiments, the flame retardant includes 120 to 200 parts of halogen-free flame retardant, 3 to 6 parts of organosilicon flame retardant and 3 to 12 parts of nano synergist, wherein the average particle size of the halogen-free flame retardant is 0.6 to 2.0 μm. The use of halogen-free flame retardant, organosilicon flame retardant and nano synergist compounding can not only reduce the total amount of flame retardant added, ensure the basic physical and chemical properties of the material such as mechanical properties, electrical properties, tear resistance, oil resistance, and low temperature resistance, but also make the material have good crusting and drip resistance, thereby significantly increasing the flame retardant properties and light transmittance of the material.
[0081] In at least some embodiments, the mixed flame retardant filler can be obtained by the following method:
[0082] 1-2 parts of the surface treatment agent are uniformly sprayed on 120-200 parts of the halogen-free flame retardant, and the mixture is placed in a high-speed mixer and mixed at a speed of 300±50 rpm for 240-300 seconds; after the mixing is completed, 3-6 parts of the organosilicon flame retardant, 3-12 parts of the nanosynergist, 1-4 parts of the antioxidant, 0.5-1.5 parts of the lubricant, 0.3-1.5 parts of the light stabilizer, 0.8-2 parts of the radiation cross-linking sensitizer, 0.53-2.1 parts of the unsaturated silane cross-linking agent and 0.32-1.05 parts of the silane cross-linking initiator are added, and the mixture is continuously mixed for 100-120 seconds to obtain a first mixed flame retardant filler;
[0083] 1-2 parts of the surface treatment agent are uniformly sprayed on 120-200 parts of the halogen-free flame retardant, and the mixture is placed in a high-speed mixer and mixed at a speed of 300±50rpm for 240-300s; after the mixing is completed, 3-6 parts of the organosilicon flame retardant, 3-12 parts of the nanosynergist, 1-4 parts of the antioxidant, 0.5-1.5 parts of the lubricant, 0.3-1.5 parts of the light stabilizer, 0.8-2 parts of the radiation cross-linking sensitizer and 10-60 parts of the silane cross-linking catalyst are added, and the mixture is continuously mixed for 100-120s to obtain a second mixed flame retardant filler;
[0084] Among them, the surface treatment agent is at least one of a vinyl silane coupling agent, an amino silane coupling agent and a titanate coupling agent. The surface treatment agent is used to pre-treat the surface of the flame retardant and other powder base materials, which can improve the compatibility between the resin matrix and the powder filler, thereby improving the dispersibility of the powder filler and improving the mechanical properties and flame retardant properties of the material.
[0085] The antioxidant is a mixture of antioxidant 1010, antioxidant 168, antioxidant S35 and antioxidant DNP in a mass ratio of 1.0:0.5:(0.5-1.5):(0.3-1.0);
[0086] The light stabilizer is one or two of UV944, UV328, UV1164 and 2020; the lubricant is one or two of polyethylene wax, zinc stearate and oleic acid amide; the radiation cross-linking sensitizer is at least one of triallyl isocyanurate (TAIC) and trimethylolpropane trimethacrylate (TMPTMA); the unsaturated silane cross-linking agent is one or two of vinyl trimethoxysilane, vinyl methyl dimethoxysilane and octyl triethoxysilane; the silane cross-linking initiator is an organic peroxide; the silane cross-linking catalyst is at least one of dibutyl tin dilaurate, dialkyl tin mercaptide and stannous 2-ethylhexanoate.
[0087] In at least some embodiments, double cross-linking is performed by the following method to obtain a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material:
[0088] The first mixed flame retardant filler, the resin base material, the maleic anhydride grafted material, the hollow glass microspheres and the silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of (126-218):(55-152):(5-12):(3-8):(4-8), mixed, extruded and granulated, and recorded as material A;
[0089] The second mixed flame retardant filler, resin base material, maleic anhydride grafted material, hollow glass microspheres and silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of (126-218):(55-152):(5-12):(3-8):(4-8), mixed, extruded and granulated, and recorded as material B;
[0090] The A material and B material obtained above are evenly placed in a 130°C internal mixer in a mass ratio of 95:5 for mixing and kneading, the mixer is opened for sheeting, and the flat plate vulcanizer is used for sheeting to prepare a halogen-free flame-retardant cable material. The above-mentioned sheeted cable material is placed in a standard environment (temperature 23°C, humidity 45%) for 24 hours for silane self-crosslinking; after the silane self-crosslinking is completed, the sample is subjected to electron beam irradiation crosslinking, and the irradiation process is 28 passes, energy 2.0 mev, flow rate 12 mA, and speed 35 m / min. After irradiation, the heat extension is 15% to 25%, and a high tear resistance, high oil resistance, double cross-linking, low smoke, halogen-free flame-retardant cable material can be obtained.
[0091] Preferably, the temperature of the front roller of the mixing mill is set at 128°C, the temperature of the rear roller is set at 130°C, and the speed of the double rollers is 40 rpm; the temperature of the flat plate vulcanizer is set at 175°C, and the pressure is maintained for 10 minutes and pressurized for 5 minutes during sheeting;
[0092] In at least some embodiments, the high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material can be used in cables. When used in cables, the prepared A material and the B material are mixed in a blender at a mass ratio of 95:5, and the mixed cable material is placed in a coating extruder for extrusion, and the extruded cable is placed in a standard environment (temperature 23±2°C, humidity 45%~55%) for 24 hours for silane self-crosslinking. After the crosslinking is completed, the sample is subjected to electron beam irradiation cross-linking, and the irradiation process is 28 passes, 2.1 mev energy, 26 mA flow rate, and 70 m / min speed. After the irradiation, a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable is obtained.
[0093] Preferably, the extrusion temperature of the coating extruder is set at 130-140°C in zone 1, 140-150°C in zone 2, 145-155°C in zone 3, 155-165°C in zone 4, and 160-170°C in the die head.
[0094] The technical solution of the present application will be further explained below in conjunction with specific embodiments.
[0095] Embodiment 1:
[0096] A high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material is prepared by the following method.
[0097] S1, preparing a resin base material;
[0098] In parts by weight, 20 parts of ethylene-ethyl acrylate copolymer (EEA), 20 parts of ethylene-butyl acrylate copolymer (EBA), 17 parts of ethylene-glycidyl methacrylate-vinyl acetate terpolymer (E-GMA-VA), 20 parts of metallocene-catalyzed polyethylene and 15 parts of medium-density polyethylene are fully mixed, placed in a twin-screw extruder silo, fed through a loss-in-weight scale, and extruded, granulated and dried to obtain a resin base material.
[0099] S2, preparing a mixed flame retardant filler;
[0100] 1.2 parts of the surface treatment agent are uniformly sprayed on 147 parts of the halogen-free flame retardant, and the mixture is placed in a high-speed mixer and mixed at a speed of 300±50 rpm for 240 to 300 seconds; after the mixing is completed, 5 parts of the organosilicon flame retardant, 6 parts of the nanosynergist, 1.5 parts of the antioxidant, 0.9 parts of the lubricant, 1.0 parts of the light stabilizer, 1.2 parts of the radiation cross-linking sensitizer, 0.74 parts of the unsaturated silane cross-linking agent and 0.53 parts of the silane cross-linking initiator are added, and the mixture is continuously mixed for 100 to 120 seconds to obtain a first mixed flame retardant filler;
[0101] 1.2 parts of surface treatment agent are evenly sprayed on 147 parts of halogen-free flame retardant, and placed in a high-speed mixer and mixed at a speed of 300±50rpm for 240-300s; after mixing, 5 parts of silicone flame retardant, 6 parts of nano synergist, 1.5 parts of antioxidant, 0.9 parts of lubricant, 1.0 parts of light stabilizer, 1.2 parts of radiation cross-linking sensitizer and 40 parts of silane cross-linking catalyst are added, and mixing is continued for 100-120s to obtain a second mixed flame retardant filler.
[0102] S3, preparing material A;
[0103] The first mixed flame retardant filler, the resin base material, the maleic anhydride grafted material, the hollow glass microspheres and the silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of 147:92:8:4:5 for mixing, extruding and granulating to obtain material A.
[0104] S4, preparing material B;
[0105] The first mixed flame retardant filler, the resin base material, the maleic anhydride grafted material, the hollow glass microspheres and the silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of 147:92:8:4:5 for mixing, extruding and granulating to obtain material B.
[0106] S5, tableting;
[0107] The prepared material A and material B were evenly mixed and kneaded in an internal mixer in a mass ratio of 95:5 (the temperature of the internal mixer was set at 130°C, the sheet was removed from the open mixer (the temperature of the front roller of the open mixer was set at 128°C, the temperature of the rear roller was set at 130°C, and the speed of the double rollers was 40 rpm), and the sheet was pressed into shape at 175°C in a flat vulcanizer (maintaining pressure for 10 min and pressurizing for 5 min).
[0108] S6, double cross-linking;
[0109] The obtained cable material after pressing was placed in a standard environment (temperature 23°C, humidity 45%) for 24 hours for silane self-crosslinking; after the silane self-crosslinking, the sample was crosslinked by electron beam irradiation, and the irradiation process was 28 passes, energy 2.0 mev, flow rate 12 mA, speed 35 m / min. After irradiation, the thermal extension was 15% to 25%, and a high tear resistance and high oil resistance double crosslinked low smoke halogen-free flame retardant cable material was prepared.
[0110] Embodiment 2:
[0111] This embodiment prepares a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, which is different from Example 1 only in that the amount of the unsaturated silane cross-linking agent is 1.2 parts, the amount of the silane cross-linking initiator is 0.8 parts, and the amount of the silane cross-linking catalyst is 1.0 parts.
[0112] Embodiment 3:
[0113] This embodiment prepares a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, which is different from Example 1 only in that the amount of the unsaturated silane cross-linking agent is 1.2 parts, the amount of the silane cross-linking initiator is 0.8 parts, the amount of the silane cross-linking catalyst is 1.0 parts, and the amount of the hollow glass microspheres is 0 parts.
[0114] Embodiment 4:
[0115] A high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable is prepared by the following method.
[0116] S1, preparing a resin base material;
[0117] In parts by weight, 20 parts of ethylene-ethyl acrylate copolymer (EEA), 20 parts of ethylene-butyl acrylate copolymer (EBA), 17 parts of ethylene-glycidyl methacrylate-vinyl acetate terpolymer (E-GMA-VA), 20 parts of metallocene-catalyzed polyethylene and 15 parts of medium-density polyethylene are fully mixed, placed in a twin-screw extruder silo, fed through a loss-in-weight scale, and extruded, granulated and dried to obtain a resin base material.
[0118] S2, preparing a mixed flame retardant filler;
[0119] 1.2 parts of the surface treatment agent are uniformly sprayed on 147 parts of the halogen-free flame retardant, and the mixture is placed in a high-speed mixer and mixed at a speed of 300±50 rpm for 240 to 300 seconds; after the mixing is completed, 5 parts of the organosilicon flame retardant, 6 parts of the nanosynergist, 1.5 parts of the antioxidant, 0.9 parts of the lubricant, 1.0 parts of the light stabilizer, 1.2 parts of the radiation cross-linking sensitizer, 0.74 parts of the unsaturated silane cross-linking agent and 0.53 parts of the silane cross-linking initiator are added, and the mixture is continuously mixed for 100 to 120 seconds to obtain a first mixed flame retardant filler;
[0120] Spray 1.2 parts of the surface treatment agent evenly on 147 parts of the halogen-free flame retardant, and place it in a high-speed mixer and mix it at a speed of 300±50rpm for 240-300s; after mixing, add 5 parts of silicone flame retardant, 6 parts of nano synergist, 1.5 parts of antioxidant, 0.9 parts of lubricant, 1.0 part of light stabilizer, 1.2 parts of radiation cross-linking sensitizer and 40 parts of silane cross-linking catalyst, and continue mixing for 100-120s to obtain a second mixed flame retardant filler.
[0121] S3, preparing material A;
[0122] The first mixed flame retardant filler, the resin base material, the maleic anhydride grafted material, the hollow glass microspheres and the silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of 147:92:8:4:5 for mixing, extruding and granulating to obtain material A.
[0123] S4, preparing material B;
[0124] The first mixed flame retardant filler, the resin base material, the maleic anhydride grafted material, the hollow glass microspheres and the silicone masterbatch are placed in a reciprocating mixing extruder in a mass ratio of 147:92:8:4:5 for mixing, extruding and granulating to obtain material B.
[0125] S5, extruded cable;
[0126] The prepared material A and material B are mixed evenly in a mixer at a mass ratio of 95:5, and the mixed cable material is placed in a coating extruder for extrusion. The extrusion temperature of the coating extruder is set to 130-140°C in zone one, 140-150°C in zone two, 145-155°C in zone three, 155-165°C in zone four, and 160-170°C in the die head.
[0127] S6, double cross-linking;
[0128] The extruded cable was placed in a standard environment for 24 hours for silane self-crosslinking. After the crosslinking was completed, the sample was electron beam irradiation crosslinked. The irradiation process was 28 passes, 2.1 meV energy, 26 mA flow rate, and 70 m / min speed. After the irradiation, a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable was obtained.
[0129] Comparative Example 1:
[0130] This comparative example prepares a double-crosslinked flame-retardant cable material by the following method, which is different from Example 1 only in that the resin base material only includes 57 parts of ethylene-vinyl acetate copolymer (EVA), 20 parts of metallocene-catalyzed polyethylene and 15 parts of medium-density polyethylene.
[0131] Comparative Example 2:
[0132] This comparative example prepares a flame retardant cable material, which is different from Example 1 only in that only the silane self-crosslinking step is performed, that is, the sheet-formed material is placed under a standard environment (temperature 23°C, humidity 45%) for 24 hours for silane self-crosslinking to obtain the flame retardant cable material.
[0133] Comparative Example 3:
[0134] This comparative example prepares a flame retardant cable material, which is different from Example 1 only in that only the radiation cross-linking step is performed, that is, the sheet-formed material is radiation cross-linked to obtain the flame retardant cable material.
[0135] Performance test experiment 1:
[0136] The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable materials prepared in Examples 1 to 3 were used as samples, and the flame retardant cable materials prepared in Comparative Examples 1 to 3 were used as reference products. The performance indicators of all samples and reference products were tested to determine whether all samples and reference products could meet the actual use requirements. The test results are shown in Table 1 below.
[0137] Table 1 Performance test results-1
[0138]
[0139]
[0140] Among them, the mechanical properties test is carried out according to the standard GB / T 1040; the heat aging test is carried out according to the standard GB / T 2951.12 (136±2℃, 7×24h); the crosslinking degree performance test is carried out according to the reference standard GB / T 2951.21 (20N / cm 2 , 200℃×15min); low temperature tensile test refers to standard GB / T2951.14-2008, (-30±3℃); electrical performance test is carried out in accordance with standard GB / T1410; oil resistance test is carried out in accordance with standard GB / T 2951.21.
[0141] From the comparative data in Table 1, it can be seen that the high tear resistance and high oil resistance double cross-linked low-smoke halogen-free flame retardant cable material prepared in the present application has obvious improvements in mechanical properties, aging properties, hot oil resistance, tear resistance and flame retardant properties compared with the flame retardant cable material prepared by using EVA as the resin base material (Comparative Example 1) and only performing silane self-crosslinking (Comparative Example 2) and only performing radiation crosslinking (Comparative Example 3).
[0142] This is because the present application selects three ethylene copolymers with long side chain structures, namely EEA, EBA and E-GMA-VA, for compounding. EEA not only has a high melting point, but also has the highest toughness and softness among polyolefin resins. Compared with EVA, it has higher toughness and better thermal stability. EBA itself has high strength and wear resistance and excellent tear resistance. The compounding of EEA with high and low EA content and EBA with high and low BA content can not only ensure the mechanical properties of the material, but also improve the polarity of the resin base material and thus improve the compatibility with flame retardant fillers. At the same time, according to the hydrophilic and oleophobic characteristics of the polar groups, the oil resistance of the material can be improved, high EA and high BA contents can provide support for the softness of the material, and the addition of EBA can extend the service life of the material. E-GMA-VA is a terpolymer with high reactivity, which can improve the cross-linking efficiency in the later stage and provide support for a more stable network structure. At the same time, E-GMA-VA has high adhesion, which can better connect the functions of the components in series and improve the comprehensive performance of the material.
[0143] At the same time, the present application adopts a double cross-linking method to prepare cable materials, that is, in the early stage, the silane self-crosslinking method is first used to allow the material to have a preliminary cross-linking network, and in the later stage, the irradiation cross-linking method is used to improve the three-dimensional network structure of the material, thereby improving the uniformity of the microscopic network structure, so that it forms a highly elastic, strong, and well-structured CC bond and Si-O-Si bond interlaced inter-transfer network, thereby making the material have excellent heat oil resistance and tear resistance. In addition, the early silane self-crosslinking process needs to ensure that the material cross-linking efficiency is high, but the overall cross-linking degree does not need to be too high, and only a preliminary cross-linking framework needs to be formed. Therefore, the amount of unsaturated silane cross-linking agent and silane cross-linking initiator added in terms of silane cross-linking is greatly reduced compared with the conventional silane cross-linking process.
[0144] In addition, under the same conditions, Example 3 does not use hollow glass microspheres, and the mechanical properties, tear resistance, heat oil resistance and shrinkage properties of the flame-retardant cable material prepared are significantly lower than those of the flame-retardant cable material prepared in Example 2 using hollow glass microspheres. This is because hollow glass microspheres are typical spherical structures, which play the role of micro ball bearings in the resin and have better fluidity and dispersibility than fillers with lamellar, needle-shaped or irregular shapes. For cable materials, due to obvious transverse stretching during the extrusion production process, the material has a higher orientation along the stretching direction, especially after cross-linking, the impact of this phenomenon is more obvious. There are more cross-linked bonds in the stretching direction, but there is a lack of support for cross-linked bonds in the longitudinal direction, so it is difficult to form an interpenetrating network structure, so that the tensile strength and tear resistance in the transverse direction are affected, and this orientation also increases the degree of shrinkage of the cable in the later use process.
[0145] Hollow glass microspheres dispersed in the material can reduce the orientation produced during the stretching process, improve the isotropy of the material, and make it have an obvious mutual transmission network after cross-linking, so that the tearing path becomes rugged, delaying the development of tearing cracks, thereby improving the tearing strength of the material. It is worth noting that hollow glass microspheres, as a new type of filler, have the advantages of low density, small particle size, low dielectric constant, high fluidity, etc., and only a small amount of addition can play a significant role. However, it is rarely used in the field of cable materials. The main reason is that hollow glass microspheres are hollow spherical structures. The traditional processing method has a strong shear force, which will damage the structure of hollow glass microspheres to a certain extent. Once the hollow spherical structure of the hollow glass microspheres is destroyed, its use effect will be significantly reduced. The present invention uses hollow glass microspheres with small particle size and large wall thickness to enhance the structural stability of hollow glass microspheres during processing. The imported reciprocating mixing extruder is used for mixing and granulation to achieve an ideal plasticizing effect under a small shear force, and cooperates with the later double cross-linking process to improve the material's tear resistance, heat oil resistance, low shrinkage and other properties to a greater extent.
[0146] In addition, it can be seen from the scanning electron microscope images of each flame-retardant cable material shown in FIG1 that the three-dimensional network structure prepared by the high tear resistance and high oil resistance double cross-linked low-smoke halogen-free flame-retardant cable material of the present application is more dense and uniform.
[0147] Performance testing experiment 2:
[0148] The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable prepared in Example 4 was used as a sample, and the commercially available finished cable was used as a reference. The performance indicators of the samples and the reference were tested to determine whether all the samples and the reference could meet the actual use requirements. The test results are shown in Table 2 below.
[0149] Table 2 Performance test results-2
[0150]
[0151] From the comparative data in Table 2, it can be seen that the high tear resistance and high oil resistance double cross-linked low-smoke halogen-free flame retardant cable prepared in the present application has significantly improved mechanical properties, aging properties, hot oil resistance, tear resistance and flame retardant properties compared with commercially available finished cables.
[0152] Of course, the above embodiments are the best embodiments of this application, which are only used to illustrate the technical concept and features of this application, and their purpose is to enable people familiar with this technology to understand the content of this application and implement it accordingly, and they cannot be used to limit the protection scope of this application. Any modifications made according to the spirit of the main technical solution of this application should be included in the protection scope of this application.
Claims
1. A high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material, characterized in that: Including the following raw materials by mass: The resin base material includes 10 to 30 parts of ethylene-ethyl acrylate copolymer, 10 to 30 parts of ethylene-butyl acrylate copolymer, 10 to 30 parts of ethylene-glycidyl methacrylate-vinyl acetate terpolymer, 5 to 25 parts of metallocene catalyzed polyethylene and 15 to 25 parts of medium-density polyethylene.
2. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 1, characterized in that: The flame retardant cable material also includes:
3. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 1, characterized in that: The ethylene-ethyl acrylate copolymer is a mixture of ethylene-ethyl acrylate copolymers having an ethyl acrylate content of 15% and an ethyl acrylate content of 25% in a mass ratio of 1:
1.
4. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 3, characterized in that: The ethylene-butyl acrylate copolymer is a mixture of ethylene-butyl acrylate copolymers having a butyl acrylate content of 17% and a butyl acrylate content of 27% in a mass ratio of (1:1) to (1:2).
5. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 4, characterized in that: The ethylene-glycidyl methacrylate-vinyl acetate terpolymer contains 12% glycidyl methacrylate and 5% vinyl acetate.
6. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 2, characterized in that: The flame retardant comprises 120 to 200 parts of a halogen-free flame retardant, 3 to 6 parts of an organosilicon flame retardant and 3 to 12 parts of a nano synergist.
7. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 6, characterized in that: The average particle size of the halogen-free flame retardant is 0.6-2.0 μm.
8. The high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 7, characterized in that: The surface treatment agent is at least one of a vinyl silane coupling agent, an amino silane coupling agent and a titanate coupling agent.
9. A method for preparing a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1: Preparation of resin base The resin base material is obtained by fully mixing ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-glycidyl methacrylate-vinyl acetate terpolymer, metallocene-catalyzed polyethylene and medium-density polyethylene; Step S2: Preparation of mixed flame retardant filler Fully mixing the flame retardant, the radiation cross-linking sensitizer, the unsaturated silane cross-linking agent and the silane cross-linking initiator to obtain a first mixed flame retardant filler; Fully mixing the flame retardant, the radiation cross-linking sensitizer and the silane cross-linking catalyst to obtain a second mixed flame retardant filler; Step S3: Preparation of material A The first mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material A; Step S4: Preparation of material B The second mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material B; Step S5: Extrusion molding Blending and extruding the material A and the material B; Step S6: Double cross-linking The material extruded in step S5 is placed in an environment with a temperature of 23±2° C. and a humidity of 45% to 55% to perform silane self-crosslinking; after the silane self-crosslinking is completed, the sample is crosslinked by electron beam irradiation.
10. The method for preparing a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 9, characterized in that: In the step S2, a nano synergist, an antioxidant, a lubricant and a light stabilizer may also be added for mixing.
11. The method for preparing a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 10, characterized in that: Hollow glass microspheres and silicone masterbatch may also be added and mixed in step S3 and step S4.
12. The method for preparing a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to claim 11, characterized in that: In the step S6, the irradiation process for irradiation cross-linking is 28 passes, 2.1 meV energy, 26 mA flow rate, and 70 m / min speed.
13. Use of the high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material according to any one of claims 1 to 8 in cables, characterized in that: The following steps are involved: Step S1: Preparation of resin base The resin base material is obtained by fully mixing ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-glycidyl methacrylate-vinyl acetate terpolymer, metallocene-catalyzed polyethylene and medium-density polyethylene; Step S2: Preparation of mixed flame retardant filler Fully mixing the flame retardant, the radiation cross-linking sensitizer, the unsaturated silane cross-linking agent and the silane cross-linking initiator to obtain a first mixed flame retardant filler; Fully mixing the flame retardant, the radiation cross-linking sensitizer and the silane cross-linking catalyst to obtain a second mixed flame retardant filler; Step S3: Preparation of material A The first mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material A; Step S4: Preparation of material B The second mixed flame retardant filler, the resin base material and the maleic anhydride grafted material are mixed, extruded and granulated to obtain material B; Step S5: Extruding the Cable The material A and the material B are blended and placed in a coating machine for extrusion; Step S6: Double cross-linking The material extruded in step S5 is placed in an environment with a temperature of 23±2° C. and a humidity of 45% to 55% to perform silane self-crosslinking; after the silane self-crosslinking is completed, the sample is crosslinked by electron beam irradiation.
14. The use of a high tear resistance and high oil resistance double cross-linked low smoke halogen-free flame retardant cable material in a cable according to claim 13, characterized in that: The extrusion temperature of the extruder in step S5 is set to 130°C to 140°C for zone 1, 140°C to 150°C for zone 2, 145°C to 155°C for zone 3, 155°C to 165°C for zone 4, and 160°C to 170°C for the die.
Citation Information
Patent Citations
A cable material for photovoltaic cables and its preparation method
CN109485989B
A flame-retardant cable
CN110176329B
A high-temperature resistant and flame-retardant cable
CN114864163B
Silane crosslinking low-smoke halogen-free flame retardant polyolefin cable material with temperature-resisting grade of 125 DEG C and preparation method thereof
CN108129787A
Ultraviolet crosslinking low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof
CN112662046A